THE NUTRACEUTICAL MARKET: INTELLECTUAL PROPERTY, CLINICAL RESEARCH, AND FUTURE INSIGHTS - ADHIKARI, BISHOP; VENKATESH, D. NAGASAMY (International Journal of Applied Pharmaceutics, 2025)
The global nutraceuticals industry is a dynamic and rapidly evolving sector with diverse products, each offering numerous health benefits that significantly impact behaviours and market trends. The evaluation of patents within this industry reveals the dual nature of intellectual property rights as both a tool for fostering innovation and a potential barrier. However, with this growing recognition of these nutraceutical products face the challenges of ensuring product integrity, particularly in addressing issues such as adulteration and substandard quality. Key aspects include its market potential, nutraceutical company challenges, adulteration, intellectual property rights, and identification techniques that will ensure public access to safe and effective products. In addressing the core relationships between intellectual property rights, regulations, and safe and effective products this paper identifies several critical pathways for advancing industry practices like strengthening regulatory oversight, encouraging innovation through intellectual property rights, promoting ethical practices investing in research and development, and enhancing international collaboration. Also, it focuses on fostering a regulatory environment that promotes innovation and accessibility to its stakeholders who can ensure that nutraceutical products contribute meaningfully to public health objectives. There are several parameters like high-cost research and development, complex regulatory landscapes, consumer skepticism, and technologies like artificial intelligence and machine learning to streamline product development and help tailor strategies to address its specific needs. The insights of collaboration and innovation among international organizations are crucial to improving global health and well-being positively by shaping the future of the nutraceutical sector. Therefore, by addressing these collaboration relationships between governments, industry stakeholders, researchers, and civil society. Also, it is necessary to address the core relationship between intellectual property rights, regulation, and promotion of safe and effective nutraceutical products in this rapidly evolving industry.